Recruitment and retention of participants in UK surgical trials: survey of key issues reported by trial staff. Issue 6 (4th October 2020) - Crocker, J C; Farrar, N; Cook, J A; Treweek, S; Woolfall, K; Chant, A; Bostock, J; Locock, L; Rees, S; Olszowski, S; Bulbulia, R
Abstract: Background: Recruitment and retention of participants in surgical trials is challenging. Knowledge of the most common and problematic issues will aid future trial design. This study aimed to identify trial staff perspectives on the main issues affecting participant recruitment and retention in UK surgical trials. Methods: An online survey of UK surgical trial staff was performed. Respondents were asked whether or not they had experienced a range of recruitment and retention issues, and, if yes, how relatively problematic these were (no, mild, moderate or serious problem). Results: The survey was completed by 155 respondents including 60 trial managers, 53 research nurses, 20 trial methodologists and 19 chief investigators. The three most common recruitment issues were: patients preferring one treatment over another (81·5 per cent of respondents); clinicians' time constraints (78·1 per cent); and clinicians preferring one treatment over another (76·8 per cent). Seven recruitment issues were rated moderate or serious problems by a majority of respondents, the most problematic being a lack of eligible patients (60·3 per cent). The three most common retention issues were: participants forgetting to return questionnaires (81·4 per cent); participants found to be ineligible for the trial (74·3 per cent); and long follow-up period (70·7 per cent). The most problematic retention issues, rated moderate or serious by the majority of respondents, were participants forgetting to return questionnaires (56·4 per cent) and insufficient research nurse time/funding (53·6 per cent). Conclusion: The survey identified a variety of common recruitment and retention issues, several of which were rated moderate or serious problems by the majority of participating UK surgical trial staff. Mitigation of these problems may help boost recruitment and retention in surgical trials. Graphical Abstract: An online survey of surgical trial staff was conducted to identify key issues affecting recruitment and retention of participants in UK surgical trials. Several issues were reportedly experienced by over 70 per cent of respondents. Seven recruitment and two retention issues were rated 'moderate' or 'serious' by a majority of respondents. Lack of equipoise a common theme